NIHAO V: too big does not fail - reconciling the conflict between Lambda CDM predictions and the circular velocities of nearby field galaxies - Dutton, Aaron A.; Macciò, Andrea V.; Frings, Jonas; Wang, Liang; Stinson, Gregory S.; Penzo, Camilla; Kang, Xi (Monthly notices of the Royal Astronomical Society. Letters, 2016)
Abstract. We compare the half-light circular velocities, V1/2, of dwarf galaxies in the Local Group to the predicted circular velocity curves of galaxies in th
Im Titel ist "Lambda" als griechischer Buchstabe dargestellt
In original form 2015 October 17
Gesehen am 29.04.2020